2004
DOI: 10.1186/gb-2004-5-6-r39
|View full text |Cite
|
Sign up to set email alerts
|

Signal sequence analysis of expressed sequence tags from the nematode Nippostrongylus brasiliensisand the evolution of secreted proteins in parasites

Abstract: Signal sequence analysis of expressed sequence tags from the nematode Nippostrongylus brasiliensis and the evolution of secreted proteins in parasites

Parasitism is a highly successful mode of life and one that requires suites of gene adaptations to permit survival within a potentially hostile host. Among such adaptations is the secretion of proteins capable of modifying or manipulating the host environment. Nippos-trongylus brasiliensis is a well-studied model nematode parasite of rodents, which s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(21 citation statements)
references
References 64 publications
1
19
1
Order By: Relevance
“…These results therefore suggest that secreted proteins in Echinococcus are less evolutionarily conserved than non-secreted proteins. However, these differences in conservation are much less dramatic than previously reported for N. brasiliensis , in which 48.9% of signal positive peptides could be described as genus-specific compared to 26.8% for the dataset overall [64].…”
Section: Resultscontrasting
confidence: 69%
See 1 more Smart Citation
“…These results therefore suggest that secreted proteins in Echinococcus are less evolutionarily conserved than non-secreted proteins. However, these differences in conservation are much less dramatic than previously reported for N. brasiliensis , in which 48.9% of signal positive peptides could be described as genus-specific compared to 26.8% for the dataset overall [64].…”
Section: Resultscontrasting
confidence: 69%
“…Previously, in a transcriptomic study of the parasitic nematode Nippostrongylus brasiliensis , we noted that signal sequence-bearing proteins showed reduced evolutionary conservation [64]. This observation was confirmed and extended in a subsequent study: parasitic nematodes were found to have a greater proportion of novel, secreted proteins than free-living ones [65].…”
Section: Resultsmentioning
confidence: 53%
“…TUGs predicted to be part of gene families that arose in the last common ancestor of Nematoda or to be novel to A. crassus contained the highest proportion of genes predicted to have secretory signal peptides. This confirms observations made in a Nippostrongylus brasiliensis [71], where secreted and surface proteins were less conserved. Analysis of dn/ds (see below) across conservation categories favors the hypothesis of rapid evolution in proteins with more restricted phylogenetic origins.…”
Section: Discussionsupporting
confidence: 91%
“…Some fraction of the remaining 310 contigs may also be forward and reverse pairs, particularly those containing a large and similar number of ESTs, but we have conservatively treated each as a separate transcript (with the exception of Bp0008, which we interpret as an incompletely spliced product of the same gene as Bp0417). The redundancy of the library (which decreases to 4.7 without the rRNA transcripts and incompletely spliced EST), is higher than libraries of other invertebrate metazoans, such as the copepod Tigriopus japonicus (2.62 [35]), the cladoceran Daphnia magna (2.44 [36]), the cnidarian Cyanea capillata (2.11[37]), and the nematode Nippostrongylus brasiliensis (1.66[38]). The reason for such high redundancy is unclear; however, we hypothesize that the expression of many genes may have been depressed during starvation.…”
Section: Discussionmentioning
confidence: 96%